African Journal of Environmental Assessment and Management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The journal is published bi-annually in French and English by Logos Verlag, Berlin.Volume 1, number 1, January 1999; number 2, July 1999. 110 pp.ISSN 1436-7890.Subscriptions (for three issues). Institutions: DM240.00 o Euro 122.70 ( for Africa:...